Thermal radiation, chemical reaction, Hall and ion slip effects on MHD oscillatory rotating flow of micro-polar liquid - M. Veera Krishna; N. Ameer Ahamad; A.F. Aljohani (Alexandria Engineering Journal, 2021)
The thermal radiation, chemical reaction, Hall and ion slip impacts on double-diffusive unsteady MHD natural convective rotating flow of micro-polar fluid past a semi-infinite vertical moving porous plate under the influence of uniform transverse magnetic field with convective boundary conditions have been investigated. The entire system is assumed to fluctuate in time with invariant frequency, therefore, the solutions of the boundary layer be of the oscillatory style. The non-dimensional governing equations are solved analytically through perturbation method and discussed computationally with references to pertinent parameters. It is observed that the velocity and micro-rotation profiles increases with an increase in Hall and ion slip parameters but reverse effects are found with an increasing in viscosity ratio and chemical reaction parameter. The thermal radiation parameter is to increase the temperature profiles but reverse effect is observed with an increasing in frequency of oscillations. Further, the concentration is decreased with increase in the Schmidt number and, it is increased with increase in the chemical reaction parameter. For engineering curiosity, the local skin friction and couple stress coefficients, rate of heat and mass transfer in terms of Nusselt number and Sherwood number are obtained analytically and discussed numerically. Although it is originated that, the local Nusselt number and local Sherwood number remains constant with varying all pertinent parameters. The heat and mass transfer on MHD flows through porous media with the chemical reaction arise in many transport processes both naturally and artificially in many branches of science and engineering applications. This phenomenon plays an important role in the chemical industry, power and cooling industry for drying, chemical vapour deposition on surfaces, cooling of nuclear reactors, and petroleum industries. The Hall and ion slip effects are used in many situations in bio-medical engineering and aero-space engineering.